2011
DOI: 10.1093/cid/cir857
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Comparison of Ceftriaxone Versus Oxacillin for Osteoarticular Infections Due to Methicillin-Susceptible Staphylococcus aureus

Abstract: In this comparison of ceftriaxone versus oxacillin for MSSA osteoarticular infections, there was no difference in treatment success at 3-6 and >6 months following the completion of intravenous antibiotics. Patients receiving oxacillin were more likely to have it discontinued due to toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 22 publications
1
40
0
2
Order By: Relevance
“…Thus, Wieland et al . () and Valour et al . () reported treatment failure rates of 12.2% (5/41) and as high as 24.2% (16/66) in native MSSA BJI respectively.…”
Section: Introductionmentioning
confidence: 83%
“…Thus, Wieland et al . () and Valour et al . () reported treatment failure rates of 12.2% (5/41) and as high as 24.2% (16/66) in native MSSA BJI respectively.…”
Section: Introductionmentioning
confidence: 83%
“…On the other hand, the semisynthetic penicillins may be replaced altogether for patients who cannot be routinely monitored. Accumulating evidence suggests that cefazolin may be a better-tolerated alternative to both nafcillin and oxacillin (18,19,26,27). These findings will need to be balanced with practical considerations like cost and administration of the agents.…”
Section: Discussionmentioning
confidence: 99%
“…Although comparative data are lacking for PJIs, studies on the effectiveness of cefazolin for MSSA bacteraemias indicated that it is similar to oxacillin and better than vancomycin [13]. Ceftriaxone, dosed once daily, has recently been favourably compared with oxacillin for bone and joint infections [14] but is not frequently used among EIN members. Treatment for MRSA appears to be much more uniform, with 90% of providers choosing vancomycin as their first-line treatment option.…”
Section: Discussionmentioning
confidence: 99%